Tinje nad Loko pri Žusmu = Tinje oberhalb von Loka pri Žusmu Poznoantična in zgodnjesrednjeveška naselbina = Spätantike und frühmittelalterliche Siedlung - Ciglenečki, Slavko (Opera Instituti Archaeologici Sloveniae, 2000)
One of the most important and largest Late Roman and Early Medieval sites in the eastern Alpine region is presented in this book. Two seasons of rescue excavations have illuminated the appearance of this densely inhabited settlement, which was occupied, perhaps only with minor breaks, from the 4th- 9th centuries AD. Seven partially destroyed wooden houses, a completely preserved stone cult structure, and part of a Late Roman child cemetery have enabled, along with the incorporation of information from earlier finds, the convincing reconstruction of existence in the settlement. Part of the dwellings at Tinje can be attributed to the period of the 7th-9th centuries. The excavations at Tinje have thus to a great extent broached the central problem of Slovenian ethnogenesis: the contact between the Romanized indigenous population and the immigrants Slavs. Coarse pottery predominates among the small finds, and it is presented in detail in the book. Material for comparative analysis was included from all more important Late Roman settlements in the eastern Alpine region, and this thus represents an introduction to the study of this most often found and highly indicative material. Tinje above Loka pri Žusmu has been confirmed with these results as an archaeological site of the highest category, of crucial importance for understanding the ethnogenesis of the Slovenians.